صناديق الاستثمار ودورها في تنشيط الاستثمار في سوق الأوراق المالية دراسة التجربة المصرية - بوحسون, ياسر; زهرة, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث بالدراسة والتحليل مسألة صناديق الاستثمار ودورها في زيادة الاستثمار في سوق الأوراق المالية. ويتطرق البحث للأساس النظري لصناديق الاستثمار، أنواعها المختلفة، نشأتها، أهدافها، مميزاتها، والعلاقة بينها وبين المؤسسات المالية. ثم يدرس البحث صناديق الاستثمار في مصر، ولادتها، أنواعها، الهدف منها، ومن ثم تقييم أدائها. يخلص البحث إلى مجموعة من النتائج والاقتراحات التي تهدف إلى تقديم نصائح مفيدة تساهم بشكل جيد عند إقامة سوق مالية وصناديق استثمار في سورية. The research studies and analyzes the issue of investment funds and its role in increasing the investment in stock exchange. This research shows the theoretical basis of investment funds, their different kinds, their early life, their targets, their features and the relationship between the investment funds and financial organizations. Then the research studies the investment funds in Egypt, their birth, their kinds, their targets, then evaluates the performance of Egyptian investment funds. The research ends to some results and suggestions that aim to give useful advices which contribute well when making financial market and investment funds in Syria.